ΑEβ7 Integrin Identifies Subsets of Pro-Inflammatory Colonic CD4+ T Lymphocytes in Ulcerative Colitis. (7th December 2016) - Lamb, Christopher A.; Mansfield, John C.; Tew, Gaik W.; Gibbons, Deena; Long, Anna K.; Irving, Peter; Diehl, Lauri; Eastham-Anderson, Jeff; Price, Maria B.; O'Boyle, Graeme; Jones, David E. J.; O'Byrne, Sharon; et al.
Abstract: Background and Aims: The αEβ7 integrin is crucial for retention of T lymphocytes at mucosal surfaces through its interaction with E-cadherin. Pathogenic or protective functions of these cells during human intestinal inflammation, such as ulcerative colitis [UC], have not previously been defined, with understanding largely derived from animal model data. Defining this phenotype in human samples is important for understanding UC pathogenesis and is of translational importance for therapeutic targeting of αEβ7–E-cadherin interactions. Methods: αEβ7+ and αEβ7− colonic T cell localization, inflammatory cytokine production and expression of regulatory T cell-associated markers were evaluated in cohorts of control subjects and patients with active UC by immunohistochemistry, flow cytometry and real-time PCR of FACS-purified cell populations. Results: CD4+αEβ7+ T lymphocytes from both healthy controls and UC patients had lower expression of regulatory T cell-associated genes, including FOXP3, IL-10, CTLA-4 and ICOS in comparison with CD4+αEβ7− T lymphocytes. In UC, CD4+αEβ7+ lymphocytes expressed higher levels of IFNγ and TNFα in comparison with CD4+αEβ7− lymphocytes. Additionally the CD4+αEβ7+ subset was enriched for Th17 cells and the recently described Th17/Th1 subset co-expressing both IL-17A and IFNγ, both of which were found at higher frequencies in UC compared to control. Conclusion: αEβ7 integrin expression on human colonic CD4+ T cells was associated with increased production of pro-inflammatory Th1, Th17 and Th17/Th1 cytokines, with reduced expression of regulatory T cell-associated markers. These data suggest colonic CD4+αEβ7+ T cells are pro-inflammatory and may play a role in UC pathobiology.